Effect of Cultivars and Date of Transplanting on Growth and Productivity of Mustard in Lateritic Soil of West Bengal - De, Sandip Kumar; Sinha, Amit Kumar; Pramanik, Kalipada (International Journal of Economic Plants, 2021)
Time of sowing is one of the most important non-monetary input for crop production, particularly for rabi crops. Late harvesting of aman paddy severely affects the yield of mustard crop. Early planting through seedling of mustard can compensate the late planting at least 14 days. Under this circumstance, the use of appropriate cultivar along with timely transplanting of Indian mustard can produce higher yield under mild winter in eastern India under lateritic soil condition in late harvesting of aman paddy. A field experiment was conducted during the Rabi seasonof 2020-21 at Agricultural farm of Palli Siksha Bhavana (Institute of Agriculture), Visva-Bharati, Sriniketan, West Bengal, to study the effect of mustard (Brassica juncea L.) cultivars and date of transplanting on productivity. The experiment conducted in Factorial RBD with three cultivars viz., NRCHB 101, Kesari Gold and Kesari 5111 and four dates of transplanting viz., 3rd November, 14th November, 25th November and 6th December. Result showed that different crop cultivars and dates of transplanting significantly influenced growth and yield of mustard crop. Kesari Gold cultivar recorded maximum plant height, dry matter accumulation, leaf area plant-1, number of branches plant-1 (7.51), number of siliqua plant-1 (540.2) and number of seed siliqua-1 (13.25) and highest seed yield (1107 kg ha-1) over other two cultivars, whereas, the mustards transplanted on 3rd November recorded highest growth attributes, yield components and seed yield (1361 kg ha-1) over the other three dates of transplanting.